2018
DOI: 10.15666/aeer/1602_19351949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Seasonal Burning on Tree Species in the Guinea Savanna Woodland, Ghana: Implications for Climate Change Mitigation

Abstract: The indiscriminate burning of vegetation is a common practice in the Guinea savanna of Ghana. Burning begins at the onset of the dry season (November) and lasts until the end (April). This study investigated the effects of time of burning on tree diversity and density in the Mole National Park, Ghana. A total of 36 (10 m x 10 m) quadrats were randomly demarcated in three treatments of early and late dry season burning and non-burning study plots. Samples were taken in March, a few weeks after the late burning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The effects of wildfires, farming activities, and fuelwood extractions are likely exacerbated by the vulnerability of savannah areas, which are predominant in the northern parts of Ghana to climate change and variability as well as extreme climate events including erratic rainfall patterns, dry spells, and high temperatures [74][75][76]. Amoako et al [77] reported that fire, which is a very common tool used to burn bush to stimulate growth of fresh forage for livestock, land clearing, wild honey hunting, and for game hunting activities in the savannah areas of Ghana, has negative consequences on vegetation. They also determined that burning has a negative effect on tree density when they investigated the impacts of seasonal burning on tree species in the Guinea Savannah Woodland in the Mole National Park.…”
Section: Changes In Grassland Covermentioning
confidence: 99%
“…The effects of wildfires, farming activities, and fuelwood extractions are likely exacerbated by the vulnerability of savannah areas, which are predominant in the northern parts of Ghana to climate change and variability as well as extreme climate events including erratic rainfall patterns, dry spells, and high temperatures [74][75][76]. Amoako et al [77] reported that fire, which is a very common tool used to burn bush to stimulate growth of fresh forage for livestock, land clearing, wild honey hunting, and for game hunting activities in the savannah areas of Ghana, has negative consequences on vegetation. They also determined that burning has a negative effect on tree density when they investigated the impacts of seasonal burning on tree species in the Guinea Savannah Woodland in the Mole National Park.…”
Section: Changes In Grassland Covermentioning
confidence: 99%
“…Due to its proximity to the Sahel, the region experiences dry, dusty north-easterly winds (Harmattan) between November and April, which facilitates the annual vegetation burning [ 52 ] across all the districts in the region. The area is characterised by large areas of natural pastures with grass species from the sub-families of Andropogoneae and Paniceae [ 53 , 54 ], interspersed with fire and drought-resistant woody species from the families Fabaceae and Combretaceae [ 35 , 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…The vegetation is basically Guinea savanna which is interspersed with trees and grassland that are drought resistant. Bush fire is an annual event, which usually destroys the vegetation (Amoako et al, 2018). The fires are noted to result in substantial losses of plant nutrients, which has a negative impact on the livelihood of the people.…”
Section: On-farm Experimentsmentioning
confidence: 99%